Menggali Moderasi Beragama sebagai Pilar Keadilan: Studi Kasus Pendidikan Etika pada Mahasiswa Pascasarjana UIN Malang - Riska Khairani Nasution; Zubaidah; Siti Aisa Sanif; Rahmadani (Tasqif: Journal of Islamic Pedagogy, 2025)
This research examines the role of religious moderation as a pillar of justice in the context of ethics education among postgraduate students of UIN Malang. In an increasingly plural and complex world, religious moderation is expected to be a solution to reduce conflict and promote interfaith harmony. Through a qualitative research method with a case study type, this study conducted in-depth interviews and focus group discussions with postgraduate students to understand their understanding of religious moderation and its application in daily life. The results showed that students have a high awareness of the importance of moderation in maintaining social justice. In addition, ethics education at UIN Malang plays an important role in shaping tolerant and inclusive attitudes among students. This study concludes that the integration of religious moderation in the higher education curriculum can strengthen the values of justice and facilitate constructive interfaith dialogue.